Kitchen confidential : adventures in the culinary underbelly - Bourdain, Anthony (Harper Perennial, 2007)
A deliciously funny, delectably shocking banquet of wild-but-true tales of life in the culinary trade from Chef Anthony Bourdain, laying out his more than a quarter-century of drugs, sex, and haute cuisine - now with all-new, never-before-published material.